If $\, a\sin^2\theta+b\cos^2\theta=m$, $\, a\cos^2\phi+b\sin^2\phi=n$, $\, a\tan\theta=b\tan\phi$. Prove that


I've tried setting : $$ \frac{a}{b}=\frac{\tan\theta}{\tan\phi}=k \\ a=bk \\ \tan\theta=k\tan\phi $$

and substituting these in the equations. Can anyone tell me what I'm doing wrong ? A shorter path to the answer would also be appreciated.


$$a\sin^2\theta+b\cos^2\theta=m\to a\tan^2 \theta+b=m\sec^2\theta\\ a\tan^2\theta +b=m(1+\tan^2\theta)\to \tan^2\theta=\frac{m-b}{a-m}$$

so, using the same idea


we also have that

$$\frac{\tan^2 \theta}{\tan^2 \phi}=\frac{b^2}{a^2}$$

Can you finish?

  • $\begingroup$ Yeah. Got it. Thanks. $\endgroup$ – Vishnu V.S Mar 17 '17 at 15:19

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.